2021
DOI: 10.1371/journal.pone.0248476
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of neonatal opioid withdrawal syndrome in Arizona from 2010-2017

Abstract: In this paper, we describe a population of mothers who are opioid dependent at the time of giving birth and neonates exposed to opioids in utero who experience withdrawal following birth. While there have been studies of national trends in this population, there remains a gap in studies of regional trends. Using data from the Arizona Department of Health Services Hospital Discharge Database, this study aimed to characterize the population of neonates with neonatal opioid withdrawal syndrome (NOWS) and mothers … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…For example, prior studies from Nevada and Louisiana report that NAS was disproportionately higher among White newborns and Medicaid enrollees [ 16 , 17 ]. Eaves et al also reported that White and economically disadvantaged neonates of unmarried mothers in Arizona were more likely to be affected by opioid withdrawal [ 18 ]. Haward et al reported that the Appalachian Mountain region in North Carolina, which has been widely associated with health disparities, had a NAS incidence rate nearly three times higher than the statewide rate [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, prior studies from Nevada and Louisiana report that NAS was disproportionately higher among White newborns and Medicaid enrollees [ 16 , 17 ]. Eaves et al also reported that White and economically disadvantaged neonates of unmarried mothers in Arizona were more likely to be affected by opioid withdrawal [ 18 ]. Haward et al reported that the Appalachian Mountain region in North Carolina, which has been widely associated with health disparities, had a NAS incidence rate nearly three times higher than the statewide rate [ 19 ].…”
Section: Introductionmentioning
confidence: 99%